Clinical performance of tibia bone plate system for fixation of tibia fracture - Bhatt, Sonika; Kumar, Mohit; Kumar, Tarun; Chawale, Bhawana; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2022)
Background: In this study, we aimed to investigate the performance of the tibia plates system while treating the tibia fracture fixation. The objective of this study was to reduce the post-operative complications of proximal and distal tibia fracture by using indigenously manufactured implants (plates and screws). Methods: In this retrospective study, we studied the results of the tibia plate system in treatment of tibia fracture. A total of 34 consecutive patients were included in this study (24 males, 10 females and average age 48.6 years). Fracture type was classified as per the Muller AO classification of fracture. According to the AO classification, proximal and distal tibia fractures 41-A, 41-B and 41-C was observed with one year follow up period followed by physical exercises after one month of the surgery. The fractures were treated with wise-lock proximal and distal tibia plates. Results: The outcomes of clinical treatment were obtained in our study; no pain (88.2%), mild pain (11.7%) after 1 year follow up. The follow up of patients was taken on 1 month, 6 months and 1 year according to visual analog scale (VAS) score. No implant related problem have been found like loosening, bending and corrosion. X-ray was used to check the union, non-union. Functional outcomes were assessed with VAS. Conclusions: Treatment of tibia fracture with wise-lock proximal and distal tibia plate shows good outcomes with less complications.